The Baby Care Scale: A Psychometric Study With Fathers During Pregnancy and the Postpartum Period - Pinto, Tiago Miguel; Nunes-Costa, Rui; Figueiredo, Bárbara (Frontiers in Psychology, 2022)
The Baby Care Scale (BCS) was designed to assess father's involvement in infant care during pregnancy and the postpartum period. This study aimed to examine the psychometric characteristics of the BCS – Antenatal (BCS-AN) and - Postnatal (BCS-PN) versions. A sample of 100 primary fathers completed the BCS-AN and/or the BCS-PN, and self-reported measures of anxiety and depressive symptoms, and father-infant emotional involvement during pregnancy and the postpartum period, respectively. Good internal consistency was found for both BCS-AN and BCS-PN. A two-factor model was found for both versions of the instrument: (1) household tasks and (2) infant care tasks. The BCS-AN and BCS-PN subscales revealed good internal consistency. Higher scores on the BCS-AN predicted higher score on the BCS-PN. Significant associations were found among the BCS (BCS-AN and BCS-PN), depressive and anxiety symptoms, and father-infant emotional involvement, revealing good criterion validity. The present study suggested that the BCS-AN and the BCS-PN are reliable multidimensional self-report measures to assess father’s involvement in infant care during pregnancy and the postpartum period.